Answer:
its answer will be 9.first by using phythagorus theorem h^2=p^2+b^2'then h=15,p=12and b=x. again by putting the values of h ,p and b we get ,(15)^2=(12)^2+x^2. 225=144+x^2, x^2=225-144, x^2=81,x=√81,x=9 answer
Proof -
So, in the first part we'll verify by taking n = 1.
![\implies \: 1 = {1}^{2} = \frac{1(1 + 1)(2 + 1)}{6}](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%201%20%20%3D%20%20%7B1%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B1%281%20%2B%201%29%282%20%2B%201%29%7D%7B6%7D%20)
![\implies{ \frac{1(2)(3)}{6} }](https://tex.z-dn.net/?f=%20%5Cimplies%7B%20%5Cfrac%7B1%282%29%283%29%7D%7B6%7D%20%7D)
![\implies{ 1}](https://tex.z-dn.net/?f=%5Cimplies%7B%201%7D)
Therefore, it is true for the first part.
In the second part we will assume that,
![\: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} = \frac{k(k + 1)(2k + 1)}{6} }](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%20%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7Bk%28k%20%2B%201%29%282k%20%2B%201%29%7D%7B6%7D%20%20%7D)
and we will prove that,
![\sf{ \: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 1 + 1) \{2(k + 1) + 1\}}{6}}}](https://tex.z-dn.net/?f=%5Csf%7B%20%5C%3A%20%7B%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%201%20%2B%201%29%20%5C%7B2%28k%20%2B%201%29%20%2B%201%5C%7D%7D%7B6%7D%7D%7D)
![\: {{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 2) (2k + 3)}{6}}](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%202%29%20%282k%20%2B%203%29%7D%7B6%7D%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k (k + 1) (2k + 1) }{6} + \frac{(k + 1) ^{2} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%20%28k%20%2B%201%29%20%282k%20%2B%201%29%20%7D%7B6%7D%20%2B%20%20%5Cfrac%7B%28k%20%2B%201%29%20%5E%7B2%7D%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k(k+1)(2k+1)+6(k+1)^ 2 }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%28k%2B1%29%282k%2B1%29%2B6%28k%2B1%29%5E%202%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)\{k(2k+1)+6(k+1)\} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%5C%7Bk%282k%2B1%29%2B6%28k%2B1%29%5C%7D%20%7D%7B6%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2 +k+6k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%20%2Bk%2B6k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2+7k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%2B7k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(k+2)(2k+3) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%28k%2B2%29%282k%2B3%29%20%7D%7B6%7D%20)
<u>Henceforth, by </u><u>using </u><u>the </u><u>principle </u><u>of </u><u> mathematical induction 1²+2² +3²+....+n² = n(n+1)(2n+1)/ 6 for all positive integers n</u>.
_______________________________
<em>Please scroll left - right to view the full solution.</em>
Answer:
U=1-5(x-2)^2
Step-by-step explanation:
The equation of the parabola with vertex (h,k) is y=a(−h+x)2+k
Thus, the equation of the parabola is y=a(x−2)2+1
To find a, use the fact that the parabola passes through the point (3,−4): −4=a+1
Solving this equation, we get that a=−5
Thus, the equation of the parabola is y=1−5(x−2)^2
40,000
9,000
200
50
4
I'm guessing that's what you were looking for?